On the very idea of perfection - Stevenson, Leslie Forster (International journal of philosophy and theology, 2024)
Examining the ideal of perfection in Plato’s Forms, the Hebrew Scriptures, Anselm, Descartes, Kant’s moral philosophy, and the New Testament.